2011
DOI: 10.1111/j.1740-0929.2011.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactic acid bacteria isolated from corn stovers

Abstract: One hundred and twenty-six strains were isolated from corn stover in Henan Province, China, of which 105 isolates were considered to be lactic acid bacteria (LAB) according to Gram-positive, catalase-negative and mainly metabolic lactic acid product. Analysis of the 16S ribosomal DNA sequence of 21 representative strains was used to confirm the presence of the predominant groups and to determine the phylogenetic affiliation of isolates. The sequences from the various LAB isolates showed high degrees of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…This finding is in agreement with Pang et al . () who found carbohydrate fermentation patterns showed ambiguity. All strains were inhibited at 45°C except AZZ4 and AZZ7, while they were able to grow at pH range of 4·0–8·0.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with Pang et al . () who found carbohydrate fermentation patterns showed ambiguity. All strains were inhibited at 45°C except AZZ4 and AZZ7, while they were able to grow at pH range of 4·0–8·0.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2010) found that the number of LAB on three vegetables and other plant residue to be 10 3 -10 4 cfu g À1 , with Lactobacillus being the predominant taxa. Pang et al (2011) reported that LAB in corn stover were predominantly Lactobacillus (85.6%), consisted of L. plantarum (33.3%), L. pentosus (28.6%) and L. brevis (23.7%), and Leu. Lactobacillus accounted for 40.00%, 41.67%, 83.33% and 16.67%, while Lactococcus accounted for 60.00%, 8.33%, 16.67% and 83.33%, on MT-1, Mott, Reyan and Guimu, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that we found that the WSC content of Pennisetum grass was positively related to the abundance of LAB on Pennisetum grass, suggesting that this resources a driver of LAB populations. It is noteworthy that the number of epiphytic LAB that develop on corn, which has a high WSC content, is much higher (10 6 -10 7 cfu g À1 ) (Pang et al 2011) than that on plants such as guinea grass or naked barley straw (10 2 -10 4 cfu g À1 ), which have much lower WSC content (Zhang et al 1997. Mercier and Lindow (2000) reported that simple sugars, such as glucose, fructose and sucrose which were the main substrate for LAB fermentation, were the dominant carbon sources on the plants and were thought to simply leach from the interior of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…and an uncultured bacterium. Pang et al (2011b) identified strains isolated from maize stover, and 86% of the LAB consisted of L. plantarum, Lactobacillus pentosus and L. brevis, three species commonly reported in silages. On the other hand they reported the presence of Leuconostoc lactis, Enterococcus mundtii and Weissella cibaria, the latter a recently described species.…”
Section: New Microbial Species In Silagementioning
confidence: 99%